HUBUNGAN LIMA TIPE KEPRIBADIAN OCEAN DAN ADVERSITY QUOTIENT PADA MAHASISWA FAKULTAS ILMU SOSIAL DAN HUMANIORA DI UNIVERSITAS X - Juliadi Juliadi; Stefani Virlia (Psibernetika, 2015)
The implementation of higher education is expected to create the outstanding young generation. Therefore, success in the academic field to be relevant and important for students. However, the process of achieving success is not easy; some students got through well, but the others finally decided to escape. This research uses a quantitative approach and included in the correlational research. The sample in this study were selected using purposive sampling techniques and amounted to 162 students in the Faculty of Social Sciences and Humanities at University X. The results of this research are there is no relationship between Openness, Conscientiousness, Ekstraversion, and Agreableness personality types with adversity quotient (p> 0.05). Neuroticism personality type has a relationship with adversity quotient (p <0.05). Someone who gave negative responses to difficult situations often followed by setbacks in the different aspects of life. Some people can slowly to revive, but the others can’t. Keywords : Adversity Quotient, OCEAN Personality, Students